2022
DOI: 10.1021/acs.energyfuels.2c01176
|View full text |Cite
|
Sign up to set email alerts
|

Gas Adsorption Capacity of Type-II Kerogen at a Varying Burial Depth

Abstract: Kerogen is the main host of methane in most shale formations. Although many studies focused on its isothermal adsorption, the relationship between its methane adsorption capacity and structural characteristics has yet been well addressed. The pore structures and methane adsorption of four kinds of type-II kerogens with different maturities and at a varying burial depth are studied using a combined approach of molecular dynamics and grand canonical Monte Carlo simulations. Attributed to the combined effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
3
5
0
Order By: Relevance
“…As shown in Figure 4, Wu et al studied methane adsorption in type II kerogens at different maturities while treating both the temperature and pressure as functions of the burial depth. 92 They found a maximum capacity at a depth of 1−3 km, consistent with practical observations. In agreement with other observations on different sample types and maturities, it was also found that the porosity change does not correlate directly with an adsorption change.…”
Section: Fluid Thermodynamics and Transport In Kerogensupporting
confidence: 81%
See 4 more Smart Citations
“…As shown in Figure 4, Wu et al studied methane adsorption in type II kerogens at different maturities while treating both the temperature and pressure as functions of the burial depth. 92 They found a maximum capacity at a depth of 1−3 km, consistent with practical observations. In agreement with other observations on different sample types and maturities, it was also found that the porosity change does not correlate directly with an adsorption change.…”
Section: Fluid Thermodynamics and Transport In Kerogensupporting
confidence: 81%
“…In an attempt to move toward shale gas recovery, molecular models were also considered to investigate the gas content in kerogen in practical conditions. As shown in Figure , Wu et al studied methane adsorption in type II kerogens at different maturities while treating both the temperature and pressure as functions of the burial depth . They found a maximum capacity at a depth of 1–3 km, consistent with practical observations.…”
Section: Fluid Thermodynamics and Transport In Kerogenmentioning
confidence: 59%
See 3 more Smart Citations